Synthesis, 18F-labelling and radiopharmacological characterisation of the C-terminal 30mer of Clostridium perfringens enterotoxin as a potential claudin-targeting peptide - Löser, Reik; Bader, Miriam; Kuchar, Manuela; Wodtke, Robert; Lenk, Jens; Wodtke, Johanna; Kuhne, Konstantin; Bergmann, Ralf; Haase-Kohn, Cathleen; Urbanová, Marie; Steinbach, Jörg; Pietzsch, Jens (Amino acids, 2019)
The cell surface receptor claudin-4 (Cld-4) is upregulated in various tumours and represents an important emerging target for both diagnosis and treatment of solid tumours of epithelial origin. The C-terminal fragment of the Clostridium perfringens enterotoxin cCPE 290–319 appears as a suitable ligand for targeting Cld-4. The synthesis of this 30mer peptide was attempted via several approaches, which has revealed sequential SPPS using three pseudoproline dipeptide building blocks to be the most efficient one. Labelling with fluorine-18 was achieved on solid phase using N -succinimidyl 4-[ 18 F]fluorobenzoate ([ 18 F]SFB) and 4-[ 18 F]fluorobenzoyl chloride as 18 F-acylating agents, which was the most advantageous when [ 18 F]SFB was reacted with the resin-bound 30mer containing an N-terminal 6-aminohexanoic spacer. Binding to Cld-4 was demonstrated via surface plasmon resonance using a protein construct containing both extracellular loops of Cld-4. In addition, cell binding experiments were performed for 18 F-labelled cCPE 290–319 with the Cld-4 expressing tumour cell lines HT-29 and A431 that were complemented by fluorescence microscopy studies using the corresponding fluorescein isothiocyanate-conjugated peptide. The 30mer peptide proved to be sufficiently stable in blood plasma. Studying the in vivo behaviour of 18 F-labelled cCPE 290–319 in healthy mice and rats by dynamic PET imaging and radiometabolite analyses has revealed that the peptide is subject to substantial liver uptake and rapid metabolic degradation in vivo, which limits its suitability as imaging probe for tumour-associated Cld-4.